Life Skill of Adolescent During Pandemic Covid-19 - Ulfa Suryani; Yola Yolanda; Maulana Sidiq Pramono; Rita Angraini (Jurnal Peduli Masyarakat, 2020)
Adolescence is a period of human growth and development that occurs after childhood and before adulthood. Adolescents have a developmental task of achieving self-identity vs role confusion (doubt). The ability to achieve self-identity is carried out in a series of developmental tasks that must be completed by adolescents. The widespread spread of COVID-19 in Indonesia has an impact on all fields, especially in short-term and long-term psychosocial and mental health for children and adolescents. The purpose of conducting this counseling is to provide health education to adolescents on how to increase adolescent knowledge about life skills during the COVID-19 pandemic. The implementation of counseling on life skills for adolescents during the Covid-19 period was held on Saturday, December 26, 2020 at 10.30 WIB to 11.30 WIB. The participants of the counseling were 10 teenagers who were accompanied by 2 supervisors. The methods used in the implementation of counseling are lectures, discussions and questions and answers. The counseling begins with an opening and a pre-test is carried out in approximately 10 minutes, the delivery of material in approximately 20 minutes, a question and answer session and closing and a post-test with approximately 10 minutes. From the results of the extension evaluation, it was found that the participants were enthusiastic about extension activities. Participants are also active in asking questions to extension agents about the material presented. From the evaluation of the results, it was found that 80% of the participants could repeat the material presented.